2014
DOI: 10.3390/ijms15034837
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Hormone Secretagogue Receptor: Its Intracellular Signaling and Regulation

Abstract: The growth hormone secretagogue receptor (GHSR), also known as the ghrelin receptor, is involved in mediating a wide variety of biological effects of ghrelin, including: stimulation of growth hormone release, increase of food intake and body weight, modulation of glucose and lipid metabolism, regulation of gastrointestinal motility and secretion, protection of neuronal and cardiovascular cells, and regulation of immune function. Dependent on the tissues and cells, activation of GHSR may trigger a diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
129
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 92 publications
2
129
0
6
Order By: Relevance
“…We took advantage here of G protein activation BRET biosensors (31,32) that directly report on the conformational change of G protein upon activation, to assess whether the partial agonist behavior of these ligands toward IP1 production resulted from their G q partial agonism. Although it was reported that GHSR1a activated G protein-dependent signaling pathways through G q , G i , G o (23,30,50), and G 13 (51), these conclusions were drawn from studies that indirectly measured G protein activation. We monitored here the selective coupling of GHS-R1a to the G protein family using activation biosensors for a panel of G protein subtypes and isoforms (G q , G i1 , G i2 , G i3 , G oa , G ob , G s , G 12 , and G 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage here of G protein activation BRET biosensors (31,32) that directly report on the conformational change of G protein upon activation, to assess whether the partial agonist behavior of these ligands toward IP1 production resulted from their G q partial agonism. Although it was reported that GHSR1a activated G protein-dependent signaling pathways through G q , G i , G o (23,30,50), and G 13 (51), these conclusions were drawn from studies that indirectly measured G protein activation. We monitored here the selective coupling of GHS-R1a to the G protein family using activation biosensors for a panel of G protein subtypes and isoforms (G q , G i1 , G i2 , G i3 , G oa , G ob , G s , G 12 , and G 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…GHS-R1a is coupled to the G q signaling pathway to trigger inositol phosphate production and intracellular calcium release (23). In the context of G q signaling, an interesting particularity of GHS-R1a is its exceptionally high constitutive activity.…”
mentioning
confidence: 99%
“…The GHS-R1a ghrelin receptor subtype seems to be linked to the PLC/PKC intracellular transduction pathway (Chen et al, 2009;Grey and Chang, 2011;Yin et al, 2014). A circuitry that includes the activation of PLC and the regulation of different transcriptional factors has previously been suggested as a determinant in the modulation of the circadian system in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…goldfish), resulting in the presence of four receptor subtypes (GHS-R1a1, GHS-R1a2, GHS-R2a1 and GHS-R2a2; Kaiya et al, 2010). Among the different GHS-R subtypes, GHS-R1a seems to be involved in most of the ghrelin physiological actions (Gnanapavan et al, 2002;Kaiya et al, 2013;Yin et al, 2014). This receptor is mainly coupled to the phospholipase C (PLC)/protein kinase C (PKC) pathway (Kojima et al, 1999;Yin et al, 2014), but it can also trigger alternative intracellular pathways, including the adenylyl cyclase (AC)/protein kinase A (PKA) pathway (Kohno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin has been reported to function in the regulation of energy metabolism, food intake and body weight. It has * Author for correspondence: mfsonmez@erciyes.edu.tr also role in GH and gastric acid secretion, cell proliferation and in the protection of neuronal and cardiovascular cells (Hewson and Dickson 2000;Wren et al 2000;Asakawa et al 2001;Nakazato et al 2001;Yin et al 2014). Ghrelin has 28 amino acids, and the Ser3 residue is known to be noctanoylated (Inui 2001;Kojima et al 2001).…”
Section: Introductionmentioning
confidence: 99%